Antofagastaite, Na2Ca(SO4)2·1.5H2O, a new mineral related to syngenite. (12th December 2019) - Pekov, Igor V.; Kovrugin, Vadim M.; Siidra, Oleg I.; Chukanov, Nikita V.; Belakovskiy, Dmitry I.; Koshlyakova, Natalia N.; Yapaskurt, Vasiliy O.; Turchkova, Anna G.; Möhn, Gerhard
Abstract: The new mineral antofagastaite, ideally Na2 Ca(SO4 )2 ·1.5H2 O, was found in the oxidation zone of sulfide–quartz veins at the abandoned Coronel Manuel Rodríguez mine, Mejillones, Antofagasta Province, Antofagasta Region, Chile. It is associated with sideronatrite, metasideronatrite, aubertite, gypsum, ferrinatrite, glauberite, amarillite and an unidentified Fe phosphate. Antofagastaite occurs as prismatic crystals up to 0.5 mm × 1 mm × 5 mm, elongated along [010], typically combined in open-work aggregates up to 1 cm across. Antofagastaite is transparent and colourless, with vitreous lustre. It is brittle; the Mohs' hardness is ca 3. Cleavage is distinct on (001). D meas. is 2.42(1) and D calc. is 2.465 g cm −3 . Antofagastaite is optically biaxial (–), α = 1.489(2), β = 1.508(2), γ = 1.510(2) and 2Vmeas. = 40(10)°. The IR spectrum is reported. Chemical composition (wt.%, electron microprobe, H2 O determined by gas chromatography) is: Na2 O 20.85, CaO 17.42, SO3 52.56, H2 O 7.93, total 98.76. The empirical formula (based on 8 O atoms belonging to sulfate anions per formula unit with all H belonging to H2 O molecules) is Na2.06 Ca0.95 S2.01 O8 ·1.35H2 O. Antofagastaite is monoclinic, P 21 / m, a = 6.4596(4), b = 6.8703(5), c = 9.4685(7) Å, β = 104.580(4)°, V = 406.67(5) Å 3 and Z = 2. The strongest reflections of the powder XRD pattern [ d, Å ( I, %) ( hkl )] are: 9.17 (100) (001), 5.501 (57) (011), 3.437 (59) (020), 3.058 (43) (003), 2.918 (50) (2¯11), 2.795 (35) (013) and 2.753 (50) (121, 201). The crystal structure was solved based on single-crystal X-ray diffraction data, R 1 = 5.71%. The structure of antofagastaite consists of ordered and disordered blocks and is related to syngenite K2 Ca(SO4 )2 ·H2 O. Incorporation of additional H2 O molecules in the syngenite-type structure results in disorder of the one of the two tetrahedral sulfate groups occurring in antofagastaite. In addition to the above-reported type material, antofagastaite together with syngenite and blödite occurs in the Arsenatnaya fumarole, Tolbachik volcano, Kamchatka, Russia.